Right to Education: Scholarship to Ensure Accessibility - Timilsana, Binod Khanda (Saptagandaki Journal, 2017)
Right to education has a broad scope in human rights instruments including UDHR, 1948 and International Covenant on Economic, Social and Cultural Rights (ICESCR), 1966. Rights to education is a prime concern regarding the accessibility of education and its' compulsorily enjoyment especially in primary level, and generally technical, vocational and up to higher education. Scholarship and incentives have been considered as means to improve the access, participation, enrolment and achievement of the children from the poor and disadvantaged background. Scholarship is generally distributed in different forms of incentives as subsidies, food, dress, hostel facility, allowances, uniform, accommodation and so on. Scholarship impacts positively in accessibility features of students to enjoy rights to education because accessibility has these three overlapping dimensions: Non-discrimination, physical accessibility and economic accessibility. The Saptagandaki Journal Vol.8 2017: 23-30